Vladislav Fedorovych Babenko (to his 75th birthday) - Motorny, V. P.; Shevchuk, I. O.; Vakarchuk, S. B.; Korenovskyi, A. O.; Kofanov, V. O.; Parfinovych, N. V.; Pichugov, S. O.; Romanyuk, A. S.; Savchuk, V. V.; Serdyuk, A. S.; Skorokhodov, D. S.; Sokolenko, I. V.; et al. (Institute of Mathematics, NAS of Ukraine, 2025)
-